“YouTube sebagai media alternatif komunikasi politik: Integrasi Wacana Multimodal dalam Komunikasi Video Kampanye Politik “Prabowo-Gibran Memang Istimewa” - Jusuf Ariz Wahyuono; Eva Ulviati; Arun Panrita Arifin (Universitas Widya Mataram, 2026)
This study analyzes the multimodal discourse in Prabowo-Gibran's YouTube campaign videos. The goal is to understand how these advertising videos use various modes to construct their political meanings and messages. The object of this research is a video titled